Effective application of pneumo-vibro-massage in aesthetic gynecology - I A Apolikhina; A S Saidova; A S Chochueva; A A Churakov (IP Berlin A.V., 2017)
The use of gynecological pneumo-vibro-massage as monotherapy, or in combination with other methods of physiotherapy helps to strengthen the entire complex of metabolic and trophic processes, improve the activity of regulatory systems, and to suspend the development of muscle atrophy and sclerotic changes. Our own experience in the application of this method for gynecological diseases, showed an improvement in tissue trophism, regeneration and restoration of functions. Gynecological pneumo-vibro-massage using MKV-01 "Ivavita" in a complex treatment of various diseases can take a significant place in restorative medicine and rehabilitation.